Maternal and Child Determinants of Under-Five Mortality in India: Evidence from the National Family Health Survey (NFHS-5), 2019–21 - Ambike, Abhijit; Pati, Minakshee Jagdish; Ashtekar, Archana; Ambike, Deepali; Roshani, Akuskar; Vashishth, Tanya; Garg, Pooja; Jabade, Mangesh; Nadaf, Husain (International Journal of Statistics in Medical Research, 2026)
Background: Under-five mortality is a critical indicator of child health and overall socioeconomic development. Although India has made substantial progress in reducing child mortality, significant disparities persist across regions and population groups. This study aimed to examine the maternal and child determinants associated with under-five mortality in India using nationally representative data from the National Family Health Survey (NFHS-5, 2019–21). Methods: A cross-sectional secondary analysis of NFHS-5 data was conducted, including 237,500 live births occurring within five years preceding the survey. Under-five mortality was the outcome variable. Maternal factors (age, education, residence, wealth status, and media exposure) and child-related factors (sex, birth order, birth weight, and type of birth) were examined. Descriptive statistics, chi-square tests, and multivariable logistic regression analyses were used to identify significant determinants. Statistical significance was considered at p < 0.05. Results: The prevalence of under-five mortality was 3.8%. Mortality was significantly higher among children born to mothers with no formal education (5.5%) and those belonging to the poorest wealth quintile (6.0%). Children residing in rural areas and those born to mothers aged below 20 years experienced higher mortality rates. High birth order (≥4), low birth weight, and multiple births were strongly associated with increased risk of death before five years of age. Male children showed slightly higher mortality (4.0%) compared with female children (3.5%). Maternal exposure to mass media was associated with improved child survival. Multivariable analysis identified maternal education, household wealth, place of residence, birth weight, birth order, and type of birth as significant predictors of under-five mortality. Conclusion: Under-five mortality in India continues to be influenced by socioeconomic, maternal, and child-related factors. Improving maternal education, reducing socioeconomic inequalities, enhancing maternal and child nutrition, and strengthening access to quality healthcare and health information are essential for further reducing child mortality and achieving the Sustainable Development Goal target of fewer than 25 under-five deaths per 1,000 live births by 2030.